Climate Change Adaptation and Resiliency of Coastal Communities in the Red River Delta Biological Reserve, Vietnam - Ha, Quyen Dinh; Dizon, Josefina T.; Rola, Agnes C.; Quimbo, Maria Ana T.; Pintor, Lynlei L. (Silliman Journal, 2022)
This case study assessed the climate change adaptation and resiliency of coastal communities in Giao Thien and Giao Xuan in Giao Thuy District, Vietnam. Methods used include survey, key informant interview, and review of documents of which 194 households served as the sample size. A pretested interview schedule was used to gather data. Descriptive statistics was done to describe the data. Inferential statistics was employed in determining the relationship between climate change adaptation and resiliency. Result revealed that majority prepared materials to shield their houses, prepared food, and monitored weather bulletin. The communities received help from various organizations and have talent and skills to adjust to climate change. Majority observed that the ecosystem has worsened because of environmental pollution and lack of awareness in environmental protection. Communities perceived that the mangrove forests have the full ability to protect the environment. Coastal communities have limited knowledge on climate change adaptation. The most common plan in preparation for climate change is on house renovation. Infrastructure in the communities is not enough to cope with climate change. Natural resources have decreased because of mining, destructive fishing, and pollution which also contribute to climate change. The mangrove forest resources have the capability to combat climate change. The relationships among the climate change adaptation and resiliency variables have positive linear association, but all are found to have weak association.